ANALISIS SIKAP KONSUMEN PADA RUMAH SAKIT UMUM PKU MUHAMMADIYAH YOGYAKARTA - Anhari, Agus; Setyono, Hendro (Universitas Ahmad Dahlan, 2011)
Selective community in selecting health care must be observed and analyzed hospital. Hospital as a place to obtain medical services necessary to meet the expectations of society, as a subscription service (consumer) health. Hospitals need to know the ratio of users to health services that are more selective. Or not the positive attitude of consumers ideally clear from evaluation and their trust in the services they receive. Improved elements (attributes), such as tenderness, attention, safety and reliability of direct evidence is absolutely necessary as a measure of quality of service in the services sector.This study aims to determine consumer attitudes and the relationship between consumer confidence with consumer ratings on General Hospital PKU Muhammadiyah Yogyakarta. consumer attitudes referred to in this research is the level of feelings of patients in comparing the performance (results) are perceived with hope. So the attitude of patients is a function of the difference between the perceived performance with expectations.Consumer Attitudes towards the General Hospital of PKU Muhammadiyah Yogyakarta at 80.03 and is located in the interval from 77 to 100.9 and included in the positive category. While the relationship between assessment and the resulting consumer confidence coefficient = 0.072, Ï = 0.000 and Î± of 0.01 for Ï sig (0.000) < Î± of 0.01, it can be concluded that there is a strong relationship between consumer confidence with consumers ranking House PKU Muhammadiyah Hospital in Yogyakarta.